IMPLEMENTASI KONTRAK BISNIS TERHADAP BUDAYA LINTAS NEGARA DI JEPANG (Studi pada tenants di Connect House Co., Ltd) - Andi Mitchel Douglas; Yusri Abdillah; Brillyanes Sanawiri (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
The objective of this research is to describe how to implement the business contract in Japan and the connection with the cross cultural nation from other countries outside from Japan. This research is conducted using pure descriptive qualitative methods or phenomenology approach. This research reveals five steps to contracting as the implementation in Japan as; (1) Creating information, (2) Offer, (3) Negotiation, (4) Accepting, and (5) Completing contract. Afterwards, each country has their own custom, way, and idea which are different in the steps of implementations. Cultural approaches under this study include; (1) Individual vs collectivism to see how people make decision of negotiation; (2) Masculinity vs feminity to see the custom of tenants and company when they have to protect the consideration of contract; (3) Uncertainty avoidance to see how the behavior of people when they have to face ambiguous situation. (4) High vs low context to see how details is the contract. (5) Universalism vs particularism to see the power or position each party in the contract and; (6) internal vs external orientation to see the behavior each parties when they negotiating. Keywords: implementation, culture, negotiation, contract, tenants. ABSTRAK Penelitian ini bertujuan untuk menggambarkan bagaimana implementasi kontrak tenants di Jepang dan kaitannya dengan budaya dari berbagai negara di luar Jepang. Penelitian ini menggunakan metode kualitatif deskriptif murni atau yang biasa disebut dengan phenomenology. Hasil penelitian menunjukkan lima tahap sebagai implementasi dalam berkontrak di Jepang antara lain; (1) Creating information (2) Offer, (3) Negotiation, (4) Accepting, and (5) Completing contract. Selanjutnya pada tahap-tahap implementasi tersebut setiap negara memiliki pemikiran, kebiasaan, dan cara yang berbeda. Pendekatan budaya yang dilakukan antara lain; (1) Individualism vs collectivism untuk melihat bagaimana pengambilan keputusan dalam hasil negosiasi; (2) Masculinity vs feminity untuk melihat sikap tenant dan perusahaan menegakkan isi kontrak; (3) Uncertainty Avoidance untuk melihat perilaku masyarakat dalam menghadapi situasi yang ambigu; (4) High vs low context untuk melihat kedetilan isi kontrak; (5) Universalism vs particularism untuk melihat kedudukan kontrak dan; (6) Internal vs external orientation untuk melihat perilaku dalam bernegosiasi. Kata Kunci: implementasi, budaya, negosiasi, kontrak, tenants.